Long-acting somatostatin analogues provide significant beneficial effect in patients with refractory small bowel angiodysplasia: Results from a proof of concept open label mono-centre trial. Issue 1 (February 2016) - Holleran, Grainne; Hall, Barry; Breslin, Niall; McNamara, Deirdre
Introduction: Small bowel angiodysplasias account for over 50% of causes of small bowel bleeding and carry a worse prognosis than lesions located elsewhere in the gastrointestinal tract. Re-bleeding rates are high even after first-line endoscopic therapy and are associated with high levels of morbidity for affected patients. Small trials of long-acting somatostatin analogues have shown promising results but have not yet been assessed in patients with refractory small bowel disease. Aim: The purpose of this study was to assess the effect of long-acting somatostatin analogues in reducing re-bleeding rates and transfusion requirements, and improving haemoglobin levels in patients with refractory small bowel angiodysplasia. Methods: Patients with refractory small bowel angiodysplasia were treated with 20 mg of long-acting octreotide for a minimum of three months. Response was assessed according to: rates of re-bleeding, haemoglobin levels, transfusion requirements, and side effects. Results: A total of 24 patients were initially treated and 20 received at least three doses. Rates of complete, partial and non-response were 70%, 20% and 10% respectively. Average haemoglobin rates increased from 9.19 g/dl to 11.35 g/dl ( p  = 0.0027, 95% confidence interval (CI) −3.5 to −1.1) in the group overall and 70% remained transfusion-free after a mean treatment duration of 8.8 months. The rate of adverse events was higher than previously reported at 30%. Conclusion: Long-acting somatostatin analogues offer a therapeutic advantage in a significant proportion of patients with small bowel angiodysplasia. With careful patient selection and close observation, a long-acting somatostatin analogue should be considered in all patients with persistent anaemia attributable to refractory disease in conjunction with other standard treatments.